Determination of thermodynamic pKa values of pharmaceuticals from five different groups using capillary electrophoresis. Issue 7 (2nd March 2015) - Zrnčić, Mirta; Babić, Sandra; Mutavdžić Pavlović, Dragana
<x xml:space="preserve">Abstract</x> A determination of the thermodynamic acid dissociation constants (pKa) of 22 frequently used pharmaceuticals using capillary electrophoresis in aqueous media is presented in this work. The investigated pharmaceuticals belong to different pharmacological groups: macrolides, fluoroquinolones, sulfonamides, β‐lactams, tetracyclines, and other miscellaneous pharmaceuticals. The electrophoretic mobilities of the investigated analytes were monitored in a pH range from 2.00 to 10.82. The data were fitted with an appropriate mathematical model using a nonlinear regression analysis to obtain pKa values. Experimentally obtained data were well described by the mathematical model chosen for each analyte that was confirmed by r2 values higher than 0.99 for most of the investigated analytes. Extrapolations to zero ionic strength were used to determine the thermodynamic pKa values. Experimentally obtained acid dissociation constants were interpreted using structural formulae of investigated analytes and the moieties corresponding to specific pKa were identified.